2009
DOI: 10.1177/105268460901900501
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Leadership: How Principals and Teachers Share Transformational and Instructional Influence

Abstract: Transformational leadership by the principal appears to be a precondition of shared instructional leadership in schools, but it does not guarantee that principals and teachers will collaborate on curriculum and instruction. The present study, a content analysis of existing case studies, explores the ways in which teachers respond to transformational leadership by the principal, with attention paid to the influence and conditions that activate interdependent relationships and enhance shared transformational lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
123
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 26 publications
10
123
1
2
Order By: Relevance
“…Direction-Setting practices (a combination of goal setting and communicating high expectations) is one of four categories included in an integrated model (Printy et al, 2010) of effective school leadership developed and refined over the past 15 years by the second author and his colleagues. The other dimensions of this model include Developing People, Redesigning the Organization, and Improving the Instructional Program.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Direction-Setting practices (a combination of goal setting and communicating high expectations) is one of four categories included in an integrated model (Printy et al, 2010) of effective school leadership developed and refined over the past 15 years by the second author and his colleagues. The other dimensions of this model include Developing People, Redesigning the Organization, and Improving the Instructional Program.…”
Section: Resultsmentioning
confidence: 99%
“…With its early roots in transformational leadership theory (Podsakoff, MacKenzie, Moorman, & Fetter, 1990), this model has been subject to considerable testing with original empirical evidence (e.g., Leithwood & Jantzi, 1999a, 1999b, 2000a, 2000b and has gradually evolved to include, as well, central elements of instructional leadership. It is now an "integrated" model (Printy, Marks, & Bowers, 2010) widely used by other researchers to help frame their inquiries (e.g., Hendriks & Scheerens, 2013) and by some large education systems to guide their leadership policies (e.g., Ontario; see Leithwood, 2012) This study is the latest in a series aimed at systematically broadening and deepening the evidence about this integrated leadership model. These studies strive to move beyond the original empirical data used in the development and evolution of this leadership model.…”
Section: Introductionmentioning
confidence: 96%
“…Overall, the mediated effects of principal leadership for teacher professional learning show that the main impact of school leadership is not through direct impact on teachers but rather by creating positive school environments and human relationships in which teacher learning can thrive (Hallinger & Heck, 1998Mulford & Silins, 2003;Printy, Marks, & Bowers, 2009;Robinson et al, 2008). Trust, communication and collaboration are critical to ensure effective school functioning.…”
Section: Implications and Recommendationsmentioning
confidence: 95%
“…A similar imperative to make decisions under conditions of ambiguity applies in schools, except to an even greater degree (Deal and Celotti 1977;Weick 1976). Skilful education managers implicitly manage this ambiguity by seeking to balance autonomy and control in managing the teaching and learning processes (Cuban 1988;Leithwood, Harris, and Hopkins 2008;Lortie 1975;Robinson, Lloyd, and Rowe 2008;Printy, Marks, and Bowers 2009).…”
Section: School Alignment and Coherencementioning
confidence: 95%
“…These include research on effective schools (e.g., Edmonds 1979;Purkey and Smith 1983), instructional leadership (e.g., Hallinger, Bickman, and Davis 1996;Printy, Marks, and Bowers 2009), strategic leadership (e.g., Davies, Ellison, and Bowring-Carr 2005) and transformational school leadership (e.g., Leithwood 1994;Leithwood and Jantzi 2000). In a recent meta-analysis, Robinson, Lloyd, and Rowe (2008) examined a diverse set of leadership effects studies and found that the use of goals constituted a high-impact leadership strategy.…”
Section: Theoretical Perspectivementioning
confidence: 97%